Constitutional Conventions and the Prince of Wales. Issue 6 (1st November 2013) - Perry, Adam
Abstract : The Upper Tribunal (Administrative Appeals Chamber) held in Evans v Information Commissioner that certain correspondence between Prince Charles and government officials must be disclosed under freedom of information legislation. Much of the judgment was devoted to a discussion of the constitutional conventions applicable to Prince Charles, and the case provides a useful example of how conventions and laws can interact. In this note, I argue that the Upper Tribunal misunderstood how conventions are distinguished from one another, and misapplied the test for the identification of conventions.